An overview of fermentation in the food industry - looking back from a new perspective - Shahida Anusha Siddiqui; Zeki Erol; Jerina Rugji; Fulya Taşçı; Hatice Ahu Kahraman; Valeria Toppi; Laura Musa; Giacomo Di Giacinto; Nur Alim Bahmid; Mohammad Mehdizadeh; Roberto Castro-Muñoz (Bioresources and Bioprocessing, 2023)
Abstract Fermentation is thought to be born in the Fertile Crescent, and since then, almost every culture has integrated fermented foods into their dietary habits. Originally used to preserve foods, fermentation is now applied to improve their physicochemical, sensory, nutritional, and safety attributes. Fermented dairy, alcoholic beverages like wine and beer, fermented vegetables, fruits, and meats are all highly valuable due to their increased storage stability, reduced risk of food poisoning, and enhanced flavor. Over the years, scientific research has associated the consumption of fermented products with improved health status. The fermentation process helps to break down compounds into more easily digestible forms. It also helps to reduce the amount of toxins and pathogens in food. Additionally, fermented foods contain probiotics, which are beneficial bacteria that help the body to digest food and absorb nutrients. In today’s world, non-communicable diseases such as cardiovascular disease, type 2 diabetes, cancer, and allergies have increased. In this regard, scientific investigations have demonstrated that shifting to a diet that contains fermented foods can reduce the risk of non-communicable diseases. Moreover, in the last decade, there has been a growing interest in fermentation technology to valorize food waste into valuable by-products. Fermentation of various food wastes has resulted in the successful production of valuable by-products, including enzymes, pigments, and biofuels.